The e-learning tool Voxopop and its benefits on oral skills: activities for final year students of German - Stollhans, Sascha (Research-publishing.net, 2015)
This case study demonstrates how Voxopop, a voice based e-learning tool, can be used to practise oal skills in the target language by presenting activities which have been developed for students of German at the University of Nottingham. The focus lies on an ongoing innovative project designed to improve final year students’ oral skills by having them interact with each other on Voxopop, specifically in the context of debriefing them on their year abroad experience. Like many Internet forums, Voxopop is a platform to exchange ideas and engage in discussions. However, this is done in oral instead of written form and is therefore an opportunity to practise oral performances in the target language. The key advantage of Voxopop lies in the fact that it is self-explanatory, user-friendly and accessible online so students can use it anywhere, with minimal equipment (e.g. their laptop or smartphone). It creates an environment where students do not feel under pressure as they can practise, listen back and re-record themselves before uploading their contributions. This also gives students the opportunity to reflect on their own output and find out about their strengths and weaknesses when producing the target language orally.